Bi2O3–BiOCl/poly-m-methyl aniline nanocomposite thin film for broad-spectrum light-sensing - Ben Gouider Trabelsi Amira; Alkallas Fatemah H.; Kusmartsev Fedor V.; Rabia Mohamed (Green Processing and Synthesis)
The fabrication of a Bi(iii) oxide-Bi(iii) oxychloride/poly-m-methyl aniline (Bi2O3–BiOCl/PmMA) nanocomposite thin-film optoelectronic device capable of light-sensing across a broad spectrum, spanning both visible and ultraviolet wavelengths, has been accomplished. The synthesis of the composite has been achieved using a one-pot technique involving the direct oxidation of m-methyl aniline with ammonium persulfate ((NH4)2S2O8) in the presence of bismuth nitrate pentahydrate (Bi(NO3)35H2O). X-ray diffraction (XRD) analysis confirms the composite’s high crystallinity and compact size of 41 nm, indicative of excellent optical properties and a narrow bandgap of 2.35 eV. The optical analysis of the synthesized core–shell composite is performed using Fourier transform infrared spectroscopy (FTIR). FTIR, X-ray photoelectron spectroscopy, and XRD analysis characterize the fabricated composite’s crystalline structure. The composite has been tested electrically using the CHI608E device, demonstrating its potential for efficient light absorption and photon trapping, making it a promising candidate for advanced light sensing applications.